Pengaruh Dana Pihak Ketiga Dan Loan To Deposit Ratio Terhadap Jumlah Penyaluran Kredit - Krisdayanti, Putri; Roestiono, Harry; Suharmiati, Suharmiati (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The purpose of this research is to know the influence of Third-Party Funds and Loan to Deposit Ratio to The Amount of Loans that happened to PT Bank Negara Indonesia (Persero) Tbk, PT Bank Central Asia Tbk, PT Bank Mandiri (Persero) Tbk on 2010-2019. Data that used for this research are quantitative data which sourch from secondary data on every banks financial report. The method used in this research are multiple linear regression analysis method, T test, F test, coefficient test and coefficient of determination test. Regression analysis used to know the influence of independence variable to dependence variable with a significance value of 5 percent while the analysis of coefficient determination and determination used to know the correlation of independent variabel and dependent variabel. Based on partial hypothesis test (T test) that has been done by the author, the result show that Third-Party Fund has a significant influence to The Amount of Loans, and the Loan to Deposit Ratio (LDR) has a significant influence to The Amount of Loans. On hypotheses simultaneously test (F test), the result shows that Third-Party Funds and Interest Rate of Corporate Loans have a simultaneous effect. Key words : Third-Party Fund, Loan to Deposit Ratio (LDR) of the Amount of Loans